2012
DOI: 10.1021/jf3006728
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Antiplatelet Activity Profile of Betulinic Acid on Human Platelets

Abstract: Betulinic acid, a natural pentacyclic triterpene acid, presents a diverse mode of biological actions including anti-retroviral, antibacterial, antimalarial and anti-inflammatory activities. The potency of betulinic acid as an inhibitor of human platelet activation was evaluated and its antiplatelet profile against in vitro platelet aggregation, induced by several platelet agonists (Adenosine Diphosphate, Thrombin Receptor Activator Peptide-14 and Arachidonic Acid), was explored. Flow cytometric analysis was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Plants produce a variety of antioxidant compounds such as phenolics, alkaloids, terpenoids and polysaccharides which could attenuate oxidative damage of a tissue directly by scavenging the free radical species and/or indirectly by enhancing natural defenses of cell [5]. Furthermore, natural products have evolved through natural selection to interact with multiple targets and to modulate multiple signal transduction pathways [9]. In the past decade, a number of studies have suggested that certain bioactive chemicals present in plants may protect against immunosuppression and oxidative stress induced by Dex [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants produce a variety of antioxidant compounds such as phenolics, alkaloids, terpenoids and polysaccharides which could attenuate oxidative damage of a tissue directly by scavenging the free radical species and/or indirectly by enhancing natural defenses of cell [5]. Furthermore, natural products have evolved through natural selection to interact with multiple targets and to modulate multiple signal transduction pathways [9]. In the past decade, a number of studies have suggested that certain bioactive chemicals present in plants may protect against immunosuppression and oxidative stress induced by Dex [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, natural products have evolved through natural selection to interact with multiple targets and to modulate multiple signal transduction pathways [9]. In the past decade, a number of studies have suggested that certain bioactive chemicals present in plants may protect against immunosuppression and oxidative stress induced by Dex [9][10][11]. Quercetin, rutin and okra (Abelmoschus esculentus Linn.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study revealed that the plant-derived triterpenes and derivatives possess anti-platelet aggregation activities regardless of the agonists. Anti-platelet aggregation activities of some triterpenes have previously been reported [17,18]. The anti-platelet aggregation activity of BA/OA mixture isolated from the leaves of Callisteum viminalis has also been reported, and further separation of BA/OA mixture using open column silica gel chromatography has been unsuccessful [13].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo preclinical studies showed some remarkable anticancer effects and a complete absence of systemic toxicity in rodents [236,237]. Regarding anti-inflammatory activities, betulinic acid potently inhibits platelet aggregation and also reduced PAC-1 binding and the membrane expression of P-selectin [238], so it has potential use as an antithrombotic compound as well.…”
Section: Aidsmentioning
confidence: 99%